A Case of Pulmonary Haemorrhage and Acute Kidney Injury 2C01. (January 2014) - Bartakke, Ashish A; Muench, Christoph
Leptospirosis is a zoonotic bacterial infection with a reservoir in rodents and farm animals. It is a common disease in tropical countries but rare in the UK. The severe form (Weil's disease) caused by Leptospira is potentially fatal and includes liver failure, renal failure and haemorrhagic pneumonitis. Typical early symptoms of leptospirosis such as myalgia, headache, conjunctivitis and fever may be absent. Careful history-taking for contact with rodents or their excrement and/or farm animals should be performed to identify patients at risk for leptospirosis. Patients with pulmonary haemorrhage and kidney failure should be screened for leptospirosis. Liver failure may be attenuated or delayed by weeks. We describe a case which proved difficult to diagnose.